2002
DOI: 10.1177/107155760200900108
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnetic Resonance Imaging and Ultrasound in the Antenatal Diagnosis of Placenta Accreta

Abstract: Both MRI and US had poor predictive value in the diagnosis of placenta accreta, and further refinement in the techniques of both MRI and US is needed for these tests to be used to reliably diagnose these pathologic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 7 publications
2
47
1
6
Order By: Relevance
“…Although there still appears to be a difference of opinion in the literature regarding the accuracy of ultrasound for the diagnosis of placenta accrete. With the exception of the Lam study who reports a sensitivity of 33% [14], all other studies report a sensitivity of 77% -93% [14] [15]. Morbidity from placenta accreta is caused by problems associated with massive bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…Although there still appears to be a difference of opinion in the literature regarding the accuracy of ultrasound for the diagnosis of placenta accrete. With the exception of the Lam study who reports a sensitivity of 33% [14], all other studies report a sensitivity of 77% -93% [14] [15]. Morbidity from placenta accreta is caused by problems associated with massive bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…A positive predictive value of 78% and a negative predictive value of 94% has been reported by Finberg et al, but some of other authors suggested that sonography might detect only around 33% of cases of placenta accreta/increta. 11,12 Regarding treatment, hysterectomy is probably the best option for long-term outcome, as previously reported. 13 Numbers of attempts have been made to treat placenta increta with various drugs to allow the pregnancy to continue.…”
Section: Discussionmentioning
confidence: 71%
“…Entretanto, ainda não existem critérios para a RM 2,4 . A RM, nos últimos dez anos, se destaca como método de diagnóstico antenatal de malformações complexas e de patologias maternas na gestação, devido a não exposição à radiação ionizante e à boa resolução diagnóstica 5 .…”
Section: Introductionunclassified
“…A RM, nos últimos dez anos, se destaca como método de diagnóstico antenatal de malformações complexas e de patologias maternas na gestação, devido a não exposição à radiação ionizante e à boa resolução diagnóstica 5 . Já existem evidências na literatura de que a RM tem um papel importante no auxílio da detecção e complementa a avaliação da extensão do acretismo e do percretismo placentário; no entanto, estes estudos são limitados, pois as análises são retrospectivas e há grande variabilidade técnica 4,5 . Os critérios clínicos para suspeita de acretismo placentário foram: multiparidade, cesáreas (mais que duas), placenta prévia, placentas corporais anteriores, miomectomias e manipulações cirúrgicas prévias do útero.…”
Section: Introductionunclassified